Influence of spatial orientation training in a centrifuge on the ability of fighter pilots to assess the bank angle during flight without visual references - Brink, Andreas; Keramidas, Michail E.; Bergsten, Eddie; Eiken, Ola (Journal of neurophysiology, 2024)
Spatial disorientation is a major problem in aviation. When performing coordinated flight turns without external visual cues (e.g., flying in clouds or darkness), the pilot underestimates the aircraft bank angle because the vestibular system provides unreliable information of roll tilt. The present study demonstrates that it is possible to, in a long-arm centrifuge, train a pilot’s ability to perceive large but not discrete-to-moderate roll-angular displacements. Without visual references, nonpilots exposed to coordinated flight turns underestimate the bank angle, because of discordant information of the roll-angular displacement from the otoliths, consistently signaling vertical position, versus the semicircular canals, enabling detection of the displacement. Pilots may also use their ability to perceive the G load and knowledge of the relation between load and angle to assess the bank angle. Our aim was to investigate whether the perception of bank angle can be improved by spatial orientation training in a centrifuge. Sixteen pilots/pilot students assessed their roll tilt, in complete darkness, during both real coordinated flight turns and gondola centrifugation, at roll tilts of 30° and 60°. The experiments were repeated after a 3-wk period, during which eight of the subjects performed nine training sessions in the centrifuge, comprising feedback on roll angle vs. G load, and on indicating requested angles. Before training, the subjects perceived in the aircraft and centrifuge, respectively: 37 (17)°, 38 (14)° during 60° turns and 19 (12)°, 20 (10)° during 30° turns. Training improved the perception of angle during the 60° [to 60 (7)°, 55 (10)°; P ≤ 0.04] but not the 30° [21 (10)°, 15 (9)°; P ≥ 0.30] turns; the improvement disappeared within 2 yr after training. Angle assessments did not change in the untrained group. The results suggest that it is possible to, in a centrifuge, train a pilot’s ability to perceive large but not discrete-to-moderate roll-angular displacements. The transient training effect is attributable to improved capacity to perceive and translate G load into roll angle and/or to increased reliance on semicircular canal signals. NEW & NOTEWORTHY Spatial disorientation is a major problem in aviation. When performing coordinated flight turns without external visual cues (e.g., flying in clouds or darkness), the pilot underestimates the aircraft bank angle because the vestibular system provides unreliable information of roll tilt. The present study demonstrates that it is possible to, in a long-arm centrifuge, train a pilot’s ability to perceive large but not discrete-to-moderate roll-angular displacements.